Fibroadenoma in axillary supernumerary breast: case report - Conde, Délio Marques (2005)
CONTEXT: Supernumerary breast tissue may be affected by the same diseases and alterations that compromise topical breast tissue. Nevertheless, reports of fibroadenoma in supernumerary breast tissue in the axillae are rare. OBJECTIVE: To describe a case of fibroadenoma in an axillary supernumerary breast. DESIGN: Case report. CASE REPORT: A 39-year-old woman was referred to the gynecology and obstetrics outpatient clinic at Hospital Estadual Sumaré, complaining of bilateral axillary masses. The patient reported cosmetic problems and local pain and discomfort. On physical examination, alterations compatible with bilateral axillary accessory breasts, without palpable nodules, were observed. Supplementary examinations (mammography and ultrasonography) revealed a 1.1 cm mass in the right axillary breast. The patient underwent resection of the supernumer- ary breasts and histopathological examination revealed fibroadenoma of the right axillary breast tissue.